Psychological Transformation in Macbeth Macbeth and Lady Macbeth - Leila Tahmasebi (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
This study is a psychological exploration of two major dynamic characters in Macbeth to say Macbeth and Lady Macbeth. Famous as a scientist of human nature two major Shakespeare’s characters change during the course of events in Macbeth to portray human nature under different circumstances. Fate is another element which plays a leading role affecting the action of the play. The role of fate is marked by bringing supernatural elements to the core of the play to point to the effect of uncontrolled forces in human life. But what is most important in this study is how the characters’ hamartia leads them to their downfall eventually. Many scholars analyze Macbeth as a drama of human nature investigation. They put the main responsibility of personality decline and their doomed fortune on the shoulder of the character himself. The play’s character exploration makes us think twice about how sovereignty and power lead human beingsto corruption and reduce them to animal or even beneath animal level.